Pola Komunikasi Mahasiswa Asing Di Pesma Internasional Kh. Mas Mansyur Universitas Muhammadiyah Surakarta(Studi Deskriptif Kualitatif Pola Komunikasi Mahasiswa Asal Sudan Di Pesma Internasional KH. Mas Mansyur Universitas Muhammadiyah Surakarta) - Kusnandar, Agus; , Drs. Joko Sutarso, S.E, M. Si (2017)
Abstract Social and cultural communication processes rarely with intertwined smoothly and not without problems. In most situations, the interaction between cultural actors do not use the same language. This study aims to determine the communication patterns of foreign students in the International Pesma KH. Mas Mansyur Muhammadiyah University of Surakarta. The method used is a method of qualitative research, qualitative research study called for emphasis on field observation research methods and data in a non-statistically analyzed. The approach used in this study is the symbolic interaction approach. In this study, there are two types of data that can be collected are primary data and secondary data. Researchers make observations directly on the object of research and in-depth interviews, the authors conducted in-depth interviews directly with the parties are considered to provide and competent in accordance with the problems in this study who serve as informants. Based on the survey results revealed that the first communication patterns make an assessment prior to being in Indonesia, after being in Indonesia they experienced culture shock and how to cope with for advice to fellow foreign students how to adapt to a new culture and country. Supporting factors that make foreign students and Indonesian students can communicate and interact with both openness and mutual respect. The barriers in communication is the use of non-standard language as Indonesian rule. Keywords: communication patterns, foreigners, students